Immobilization of Dibenzalacetone on TiO2 Surface and its Potential as Anti-UV Material - Ariefin, Mokhamat; Alfanaar, Rokiy (Department of Chemistry, Faculty of Science and Technology Universitas Jambi, 2023)
Sunlight has been known to provide many benefits to human life. However, behind these benefits, there are some negative effects along with the destruction of the ozone layer and the environment on earth. One of them is exposure to ultraviolet (UV) rays which can cause several diseases such as skin cancer. One way to overcome this is by using sunscreen substances. In this study, dibenzalacetone immobilization on TiO2 has been carried out for anti-UV applications. Based on the test results using UV-Vis spectrometry, TiO2, and dibenzalacetone both have anti-UV properties with maximum peaks at wavelengths of 335 nm and 346 nm with absorbance values of 0.871 and 1.197. Immobilization of TiO2 with dibenzalacetone gives an absorbance with a value of 1.221 at a wavelength of 329. These results indicate that TiO2 immobilization with dibenzalacetone provides better anti-UV A properties than TiO2 because of the higher absorbance value.